Integrating Cangkringan’s Local Potential in Chemistry Education Concept: Is It Really Integrated? - Rizki Arumning Tyas; Wilda Muhimmatun Nisa; Jody Febriandini; Insih Wilujeng; Suyanta Suyanta (Indonesian Journal of Science and Education (IJOSE), 2021)
Indonesia is a country with very rich in local regional potential. The local potential can be utilized as one of the natural science learning sources in junior high school. One of the local potentials that can be integrated with science lessons is food. This research aimed to conduct the study, analysis, and develop science subject specific pedagogy of natural science learning integrated local food in Cangkringan Sub-District to introduce chemical materials in junior high school, namely additives in food and its impact on health. This research was research and development (R&D) with 4-D model, consist of define, design, develop, and disseminate. Product eligibility is assessed by the validator using the product feasibility assessment sheet. Product feasibility assessment scores are then classified in product rating category classification. This research results is produce science subject specific pedagogy that consist of syllabuses, lesson plans, handouts, and student worksheets. The developed syllabus gets a feasibility score of 4.00, lesson plan gets a score of 3.80, the handout gets a score of 3.60, while the student worksheet gets a score of 3.80. Based on these results, overall, the science subject specific pedagogy developed gained a very good category.